Examining parent and clinician views of a hospital-based pediatric neuropsychological service: a Canadian perspective. Issue 1 (2nd January 2022) - Ostojic-Aitkens, Dragana; Ford, Meghan K.; Cunningham, Todd; Gold, Anna; Janzen, Laura A.; Sinopoli, Katia J.; Westmacott, Robyn; Williams, Tricia S.
ABSTRACT: Understanding how pediatric neuropsychological evaluations support families and the child's medical team is an important component of ensuring evidence-based care. For the first time within a Canadian context, we investigated the impact of neuropsychological assessments on parent knowledge, advocacy, and stress and the role of socioeconomic factors in parents' perceptions of the assessment. Responses from referring clinicians were also examined. As part of a hospital quality improvement project, 91 parents of children between the ages of 3 and 17 years ( M = 8y7m; SD = 4y1m) and 45 clinician consumers (clinical staff who use neuropsychological services) completed one of two online questionnaires in English: Parent Overall Assessment of Supports and Testing, or Clinician Overall Assessment of Supports and Testing. Most parents indicated the neuropsychological evaluation promoted understanding of their child's cognitive profile and improved their ability to support their child at home and at school or in the community. Families characterized as being at higher social risk indicated that the evaluation led to more changes in how they approached their child at home than families with lower social risk status. Referring clinicians indicated neuropsychological reports were effective in communicating findings to them and patients/families. The most valuable sections of the report according to referring clinicians included the diagnosis/impression and recommendations sections. Parents and referral providers reported many benefits from the neuropsychological evaluation but also identified areas for service delivery improvement. Parent perceptions varied based on family and socio environmental factors, offering important targets for future research and clinical consideration.